Massive pleural effusion due to pancreatic pseudocyst. Issue 7 (July 1990) - Girbes, A R; Postmus, P E; Jansen, W; vd Jagt, E J; Kleibeuker, J H
Abstract : Four patients with massive pleural effusions due to pancreatic pseudocysts who were initially treated conservatively with percutaneous pleural drainage are described. In two patients the pleural effusions and the pancreatic pseudocysts disappeared, but two required surgery, in one case because conservative treatment failed and in the other at a later date for a recurrent pancreatic pseudocyst.